1993
DOI: 10.1071/wf9930031
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fuel, Weather and Fire Shape Variables on Fire-Spread in Grasslands

Abstract: Fire-spread was measured on 121 grass fires in a 2500 ha experimental site in the Northern Territory, Australia. Selected plots were harvested to alter the height, load and bulk density of the fuel-bed. Fires were lit from a line and allowed to travel up to 400 m down-wind. Fire-spread was correlated with fuel, weather and fireshape variables using multiple regression techniques. Wind speed had most effect on fire-spread. The influence of the other variables was examined after a model for wind speed and moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
250
2
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(285 citation statements)
references
References 4 publications
24
250
2
9
Order By: Relevance
“…The scatterplot in Figure 2 and the coefficient c = 3.8 fitted by non-linear least squares suggests a far more pronounced wind effect on spread fire rate than what would be predicted by surface fire behaviour models [15,21,22,28,50]. Actually, this dramatic fire response to a modest increase in wind speed is the expected trend in the region of transition between surface and crown fire in conifer stands, especially in plantations with a well-defined gap between the two fuel layers.…”
Section: Fire Behaviour and Severitymentioning
confidence: 99%
“…The scatterplot in Figure 2 and the coefficient c = 3.8 fitted by non-linear least squares suggests a far more pronounced wind effect on spread fire rate than what would be predicted by surface fire behaviour models [15,21,22,28,50]. Actually, this dramatic fire response to a modest increase in wind speed is the expected trend in the region of transition between surface and crown fire in conifer stands, especially in plantations with a well-defined gap between the two fuel layers.…”
Section: Fire Behaviour and Severitymentioning
confidence: 99%
“…Variation of humid and dry years, as has occurred in the last decades on the Hungarian Plain, results in an accumulation of vegetation material during the wet periods which can easily catch fire during the dry periods, especially in the drought-sensitive sand vegetation. There were extensive wildfire events in the Kiskunsa ag National Park (Hungary) in the area of Kiskunsa ag Sand Ridge in 1976, 1993, which caused considerable damage to expansive areas of the national park. Extensive fires are expected to become more frequent due to climate change, as has similarly occurred in the Mediterranean (Veblen, Baker, and Montenegro, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of dry biomass could increase significantly from April to July only with a lack of herbivory in the control patches, because grazing treatments removed approximately 50% of the green vegetation, resulting in less litter on the grazed patches during the early summer. Cheney, Gould, and Catchpole (1993) found that wind speed is the most important factor ruling fire-spread. In contrast with his results, we found that the amount and height of the above-ground vegetation correlate with the burnt area and the speed of fire-spread.…”
mentioning
confidence: 99%
“…Comparison of results from a set of experimental fires in northern Canada with the predicted probabilities of fatal and non-fatal injuries calculated using the empirical models developed in the present study Survivability, as defined by Baxter (2009Baxter ( , 20102012a, 2012b, is most directly related to the probability of a fatal injury, that is, the probability that a firefighter would not survive an entrapment. 1993;Catchpole et al 1998;Frankman et al 2013). Slope and wind can alter flame geometry through changes in flame angle, which increases flame length (Weise and Biging 1996) and heat transfer by radiation (Albini 1985).…”
Section: Discussionmentioning
confidence: 99%